Plantain (Musa X paradisiaca AAB) and Activated Charcoal Powder towards Ice Cream Quality - Nurul Hidayah, Dina Mazida; Hariyani, Nunuk; Djauhari, Arlin Besari (Universitas Dr Soetomo, 2020)
Ice cream is a frozen snack made from ingredients such as milk, cream, sugar, and stabilisers that being frozen and mixed with other ingredients to create a variety of ice cream flavours, such as banana ice cream. Plantain (Musa paradisiaca) contains high nutritions such as vitamin A, B6, C, other minerals, and carbohydrates. The addition of plantain and Activated Charcoal Powder (ACP) into the ice cream can increase its nutrition value. This because of bananas as a carbohydrate source and the ACP, made from coconut shell charcoal and create a distinct ice cream colour, as a toxin absorber and immune system enhancer. This research will utilise the Completely Randomised Design (CRD) using two factors. Factor 1 is the plantain substitutions, which are 10%, 15%, and 20%. Factor 2 is the ACP concentrations, which are 0.1%, 0.2%, and 0.3%. Each combination of treatments is conducted through three-time repetitions. Research observation uses proximate analysis and organoleptic test. Parametric data in the analysis, which based on the parametric statistic by utilising Analysis of Variance (ANOVA) shows that the difference between plantain substitution and ACP concentration intangibly influences the protein and fat content. The different plantain substitution and its interaction between the different ACP concentration intangibly influence the sugar content and overrun. The different concentration of ACP intangibly influences the sugar count and tangibly influences the banana ice cream's overrun. Parametric data test results later become the base of effectivity test to obtain the best treatment. The best treatment of this research is obtained from the combination of 20% plantain and 0.3% ACP concentration, with the highest score of 0.84 with the research variable criteria of protein content (3.7%), fat content (2.4%), sugar content (41.3%), and overrun (81.37%).